Bone regeneration of the post-extraction surgical bed of molars included through plasma rich in fibrin and xenograft. Case Report - Jurado Alvear, Bryan David (2021)
The present case concerns a 22-year-old male patient with no relevant medical history who attended the SERODU dental clinic requesting the exodontics of his lower third molars. The clinical examination shows no pain to percussion, presents discomfort in the region of the third molars at the level of the gum versus palpation. In the radiographic and tomographic examination, dental organ 37 in transverse position, 38 inverted and 48 included are identified. The treatment of choice was to perform the complex extraction of the dental organs and after that, place fibrin-rich plasma in the alveolus of organ 48 and fibrin-rich plasma with xenograft in the contralateral alveolus. Clinical and radiographic controls were performed every 30 days to demonstrate the efficacy of the use of plasma rich in fibrin and xenograft in the quality of bone regeneration and its prognosis after extraction. In order to clinically and radiographically demonstrate the efficacy of fibrin-rich plasma vs fibrin-rich plasma with xenograft in the processes of healing and alveolar bone regeneration post exodontics.